The Relationship Between Financial Markets and Monetary Economics - Zakaria Zakaria; Abdul Rasyid; Ismail Noy; Rofiqah Al Munawwarah (Pascasarjana STIE Amkop Makassar, 2024)
This study investigates the intricate relationship between financial markets and monetary economics, aiming to analyze its dynamics and implications comprehensively. The research synthesizes theoretical frameworks encompassing monetarist, New Keynesian, and behavioral economics perspectives alongside empirical evidence on market reactions to monetary policy and the effectiveness of unconventional measures. Critical debates on forward guidance and financial market imperfections are explored, highlighting challenges and opportunities for policy effectiveness. Employing a mixed-methods approach, quantitative analysis and qualitative insights from market participants elucidate the nuanced mechanisms underlying this relationship. Findings underscore the pivotal role of central bank actions in shaping financial market outcomes and investor behavior, emphasizing the importance of effective communication and policy frameworks. Implications for monetary policy formulation and financial stability are discussed, emphasizing the need for transparent communication and policy frameworks to foster well-functioning financial markets and support macroeconomic stability.